Rescuing intraspecific variation in human-impacted environments - Carvalho, Carolina da Silva [UNESP] (2021)
Anthropogenic activities influence ongoing selective regimes leading to changes in phenotypic variation of plants and animals. The reduction of phenotypic variation may decrease populations' ability to cope with environmental changes. To counteract the increasing risk of extinction of affected populations, it is important to rescue intraspecific variability, assuring higher success of establishment and persistence under global changes. We evaluated whether it is possible to revert phenotypic changes caused by humans using as study case a bird-dispersed palm that presents seed size reduction due to defaunation of large-gaped frugivores. We investigated how defaunation changes the seed size profile of each population by evaluating the coefficient of variation, mean and percentage of large phenotypes of produced and dispersed seed sizes. Simple theoretical models were used to simulate the success of two restoration strategies: (a) direct reintroduction of missing phenotypes that were originally found in the species and (b) reintroduction of large-bodied frugivores to restore the ecological function of large-seed dispersal. Here we discuss the importance of rescuing phenotype states in restoration strategies. We found that defaunation changes the seed size profile by reducing the size of produced and dispersed seeds. By adding missing phenotypes one time, population mean seed size decreased back to phenotypically depauperated scenarios in eight generations. Conversely, large seed sizes could be rescued in approximately five generations after seed dispersal processes generated by large seed dispersers were re-established. To rescue and sustain phenotypes such as large seed sizes in palm populations is necessary to restore the seed dispersal processes by large frugivores or add missing phenotypes continuously over time. The restoration of the seed dispersal processes by large frugivores has additional value over seed addition because it would benefit other bird-dispersed species and, therefore, may be crucial to face ongoing global change scenarios. Synthesis and applications. Defaunation leads to character displacement within decades, having impact on populations, species and ecosystems. To prevent species extinction is paramount that phenotype variation is preserved. We propose the inclusion of phenotype restoration of wild populations as a goal for restoration framework.